Influence of chelated microfertilizers on growth processes and yield of table watermelon under agricultural conditions of the Volgograd Volga region - E. A. Galichkina; S. M. Nadezhkin (Овощи России, 2023)
Relevance. The Volgograd region is a region of risky farming. In the spring-summer period, the cultivated crop (melons) is often exposed to stress factors: spring frosts, abnormal heat, temperature changes, which negatively affects the growth and development of plants. In this regard, it is necessary to develop new adaptive agrotechnical methods for the cultivation of melons and gourds in order to obtain stable yields of high quality.Material and methodology. The object of research is watermelon, variety Meteor. Water-soluble fertilizers were studied – Helaton Extra and Aquarin vegetable for soaking seeds before sowing and foliar treatment of plants during the growing season.Results. During the research period of 2019-2021, new types of microfertilizers were studied.When using preparations Aquarin vegetable and Helaton Extra for different methods of processing, a positive effect on the growth and development of table watermelon plants, as well as on the increase in the leaf plate, was noted. Helaton Extra for soaking seeds and treating plants had the maximum impact on the growth processes of early table watermelon. As a result of the research, the yield of the studied variety also increased. The average weight of the fetus in all variants increased compared to the control variant by 2.7-5.3%. The length of the growing season in all variants increased from 2 to 4 days, which favorably affected the increase in yield. Comparative analysis of growth processes and productivity of watermelon variety Meteor when using new forms of water-soluble fertilizers for seed soaking and foliar treatment of plants showed greater efficiency from their use.